Implementation of a lifestyle intervention for people with a severe mental illness (SMILE): a process evaluation - Florine S. Walburg; Johanna W. de Joode; Hella E. Brandt; Maurits W. van Tulder; Marcel C. Adriaanse; Berno van Meijel (BMC, 2022)
Abstract Background Several interventions have been developed to improve physical health and lifestyle behaviour of people with a severe mental illness (SMI). Recently, we conducted a pragmatic cluster-randomised controlled trial which evaluated the effects of the one-year Severe Mental Illness Lifestyle Evaluation (SMILE) lifestyle intervention compared with usual care in clients with SMI. The SMILE intervention is a 12-month group-based lifestyle intervention with a focus on increased physical activity and healthy food intake. The aim of the current study was to explore the experiences of people with SMI and healthcare professionals (HCPs) regarding implementation feasibility of the SMILE intervention and the fidelity to the SMILE intervention. Methods A process evaluation was conducted alongside the pragmatic randomized controlled trial. The experiences of clients and HCPs in the lifestyle intervention group were studied. First, descriptive data on the implementation of the intervention were collected. Next, semi-structured interviews with clients (n = 15) and HCPs (n = 13) were performed. Interviews were audiotaped and transcribed verbatim. A thematic analysis of the interview data was performed using MAXQDA software. In addition, observations of group sessions were performed to determine the fidelity to the SMILE intervention using a standardised form. Results Ten out of 26 HCPs who conducted the group sessions discontinued their involvement with the intervention, primarily due to changing jobs. 98% of all planned group sessions were performed. Four main themes emerged from the interviews: 1) Positive appraisal of the SMILE intervention, 2) Suggestions for improvement of the SMILE intervention 3) Facilitators of implementation and 4) Barriers of implementation. Both clients and HCPs had positive experiences regarding the SMILE intervention. Clients found the intervention useful and informative. The intervention was found suitable and interesting for all people with SMI, though HCPs sometimes had to tailor the intervention to individual characteristics of patients (e.g., with respect to cognitive functioning). The handbook of the SMILE intervention was perceived as user-friendly and helpful by HCPs. Combining SMILE with daily tasks, no support from other team members, and lack of staff and time were experienced as barriers for the delivery of the intervention. Conclusion The SMILE intervention was feasible and well-perceived by clients and HCPs. However, we also identified some aspects that may have hindered effective implementation and needs to be considered when implementing the SMILE intervention in daily practice.